Temperament Upregulates Mitochondrial Enzymes and Negatively Affects Myofibrillar Fragmentation in Beef of Excitable Bos taurus indicus Cattle - Patricia Maloso Ramos; Eduardo Francisquine Delgado; Ana Cláudia da Silva; Nara Regina Brandão Cônsolo; Vinicius Laerte Silva Herreira; João Marcos Bovetto de Campos Valim; Fernanda Maria Marins Ocampos; Luiz Alberto Colnago; Saulo da Luz e Silva (Metabolites)
Background: Bos taurus indicus cattle is known to be temperamental and to produce beef with greater variability in terms of quality compared to beef of Bos taurus taurus. Cattle adaptability and resilience are of great importance to sustain beef production worldwide. Objective: The study aimed to understand early post-mortem metabolites among muscles with different fiber types profile of calm and excitable Nellore, as well as its relationship with fragmentation of beef aged up to 28 d. Methods: Animals were evaluated based on chute score and exit velocity to calculate a temperament index, which was used to classify them as calm or excitable. At slaughter, the pH and temperature declines of Triceps brachii (TB) and Longissimus lumborum (LL) were measured, muscles were sampled, and aged up to 28 d. Metabolites were determined, and sarcomere length and myofibrillar fragmentation index (MFI) were quantified. Metabolomics data were analyzed using a multivariate approach, while other traits were investigated through ANOVA. Results: The pH decline was affected by all three fixed effects investigated (temperament × muscle × time post-mortem: p = 0.016), while temperature decline was affected by muscle × time (p < 0.001). Metabolites differed among muscles and cattle temperament, with excitable cattle showing greater taurine abundance in LL, as well as greater creatine in TB 1 h post-mortem, based on the volcano plot. Sarcomere length and MFI results revealed faster and limited tenderization in excitable cattle beef. Conclusions: Altogether, results emphasized the upregulation of mitochondrial enzymes and reduced tenderization as determinants of inferior beef quality after prolonged aging in excitable cattle.